2012
DOI: 10.1016/j.watres.2011.11.038
|View full text |Cite
|
Sign up to set email alerts
|

A compartmental model to describe hydraulics in a full-scale waste stabilization pond

Abstract: Este documento contiene información de prueba. Contáctese con el administrador del Centro para el acceso al documento originar del registro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 27 publications
0
36
0
3
Order By: Relevance
“…This asks for developing an inverse modelling technique for reconstructing the particle density distribution starting from the PSD difference at the top and the bottom and the travel times where sedimentation can occur. Travel times (which result in the HRT of the pond) are crucial to the operation of WSP [14][15][16], and therefore the next task will be the development of a hydraulic model in Delft3D that is able to capture actual flow conditions in the Buguruni WSP. The PSD data presented here will be used, together with a hydrodynamic model developed in Delft3D, to derive the range of densities of wastewater particles at different nodes in the Buguruni WSP and hence trace where helminth eggs are most likely to be found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This asks for developing an inverse modelling technique for reconstructing the particle density distribution starting from the PSD difference at the top and the bottom and the travel times where sedimentation can occur. Travel times (which result in the HRT of the pond) are crucial to the operation of WSP [14][15][16], and therefore the next task will be the development of a hydraulic model in Delft3D that is able to capture actual flow conditions in the Buguruni WSP. The PSD data presented here will be used, together with a hydrodynamic model developed in Delft3D, to derive the range of densities of wastewater particles at different nodes in the Buguruni WSP and hence trace where helminth eggs are most likely to be found.…”
Section: Discussionmentioning
confidence: 99%
“…Complete removal of the eggs is by sedimentation in waste stabilization ponds (WSP) [8][9][10][11] when a hydraulic retention time (HRT) of about 20 days has been achieved [9,12,13]. However, actual HRT in WSP is normally lower than the designed HRT, thereby compromising their performance [14][15][16], including the removal of helminth eggs [16]. Moreover, WSP are not designed for sedimentation, despite the universal acceptance that this is the main mechanism for helminth eggs removal, as well as a large percent of other pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be caused by the fact that the central area of the FPs had less sludge accumulation and flow turbulence, which promoted high density of algae located at this region [39]. On the other hand, the bathymetries in the study of Alvarado et al [16] on these MPs showed only a slight sludge layer growth in the maturation ponds that can be assumed negligible regarding the pond hydraulics.…”
Section: Spatiotemporal Influences On the Oxygen Dynamicmentioning
confidence: 89%
“…Compartmental modeling can be used where the incorporation of biokinetics within a CFD model would be computationally cost prohibitive and where the TIS model is not able to sufficiently describe the macro-scale mixing behavior of the complex system (Alvarado et al, 2012).…”
Section: Comparison Of the Computational Requirements Of Cfd And Simpmentioning
confidence: 99%